Hubungan Frekuensi Konsumsi Junk Food dengan Tingkat Kecemasan pada Mahasiswa Tingkat 2 Fakultas Kedokteran Universitas Islam Bandung - M. Rizki Budiman; Sastramihardja, Herri S.; Andriane, Yuke (UNISBA Press, 2024)
Abstract. Anxiety is defined as the body's response to fear, which manifests as disturbances in feelings, thoughts, attitudes, and physiological changes. One of the factors that causes anxiety is consuming foods high in fat and sugar that are contained in junk food or fast food which is food that is easy to consume. This study aims to analyze relationship between frequency of junk food consumption and anxiety level in level 2 students at the Unisba Faculty of Medicine. This research is cross sectional study with sample size of 33 second year students of FK Unisba who met the inclusion criteria. Data was collected using the Food Frequency Questionnaire (FFQ) and Hamilton Anxiety Rating Scale (HAM-A). Data were analyzed using the Spearman statistical test. The research results showed that mostly respondents consumed junk food with a frequency of 1-3 times a month. It was also found that the entire research sample had anxiety with more than half of the respondents having mild levels of anxiety and 3 had severe anxiety. The Spearman test shows p value of 0,048 (< 0,05) and R value of 0,347. There is significant relationship between frequency of junk food consumption and level of anxiety with weak correlation strength. Abstrak. Kecemasan didefinisikan sebagai respon tubuh terhadap rasa takut, yang bermanifestasi sebagai gangguan perasaan, pemikiran, sikap, dan perubahan fisiologis. Salah satu faktor penyebab munculnya kecemasan adalah konsumsi makanan tinggi lemak dan gula yang terkandung dalam junk food atau makanan cepat saji yang merupakan makanan yang mudah dikonsumsi dan dibuat. Penelitian ini bertujuan untuk menganalisis hubungan antara frekuensi konsumsi junk food dengan tingkat kecemasan pada mahasiswa tingkat 2 Fakultas kedokteran Unisba. Penelitian ini merupakan penelitian cross sectional dengan jumlah sample sebanyak 33 orang mahasiswa tingkat 2 FK Unisba yang memenuhi kriteria inklusi. Data dikumpulkan menggunakan kuisioner Food Frequency Questionnaire (FFQ) dan Hamilton Anxiety Rating Scale (HAM-A). Data dianalisis dengan uji statistik spearman. Hasil penelitian didapatkan bahwa responden yang mengonsumsi junk food dengan frekuensi 1-3 kali perbulan sebanyak 12, 1 kali perminggu sebanyak 3, 2-4 kali perminggu sebanyak 11, 1 kali perhari sebanyak 2, 2-3 kali perhari sebanyak 2, 4 kali perhari sebanyak 3. Seluruh sample penelitian memiliki kecemasan dengan lebih dari setengah jumlah responden memiliki tingkat kecemasan ringan dan kecemasan berat 3 responden. Uji spearman menunjukkan nilai p sebesar 0,048 (<0,05) dan nilai R 0,347. Terdapat hubungan yang bermakna antara frekuensi konsumsi junk food dengan tingkat kecemasan dengan kekuatan korelasi lemah.